Avaliação da bioacessibilidade in vitro de compostos fenólicos em mangaba (hancornia speciosa), seriguela (spondias purpurea) e umbu-cajá (spondias spp.) - Dutra, Rodrigo Luiz Targino (2017)
The fruit of the caatinga has aroused growing interest on the part of the food industry because of its potential health benefits. Exotic fruits such as seriguela (Spondias purpurea), umbu-cajá (Spondias spp.) and mangaba (Hancornia speciosa) are important sources of bioactive compounds, such as phenolics. However, the high perishability of these fruits is a factor that hampers their in natura supply, which leads to their processing, which in turn has a direct impact on the content of bioactive present due to the process of structural modification through reactions that may interfere in the bioaccessibility of bioactive compounds, causing nutritional losses. For these reasons, the objective of this work was to determine the phenolic profile of mango, seriguela and umbu-cajá fruits and their respective pulps, evaluating the antioxidant capacity and checking the behavior of phenolic compounds when exposed to simulated gastrointestinal digestion and post-digestion bioaccessibility . In this study, phenolic compounds were identified and quantified by High Performance Liquid Chromatography (HPLC) on fruits of seriguela (Spondias purpurea), umbu-cajá (Spondias spp.) and mangaba (Hancornia speciosa), and their respective pulps and Fractions from gastrointestinal digestion. The antioxidant activity of the bioacessible fraction after in vitro simulated gastrointestinal digestion was quantified by the DPPH and FRAP assays. From the determined phenolic profile of fruits compared to their respective frozen pulps, a reduction in the phenolic compounds content of fruits of the genus Spondias spp. In the mangaba fruit there was an increase in some increased free phenolic contents, such as 3,4-dihydroxybenzoic acid (+ 50%), and p-coumaric acid (+ 50%). In the fruit pulp the reduction of the phenolic compounds was observed in front of the antioxidant tests, in which the free radical scavenging capacity reduced after the fruit processing. From the simulated gastrointestinal digestion it was observed that fruits of the genus Spondias have a high fraction of their bioaccessible phenolic compounds after digestion, with a bioaccessibility of 73.92% (gallic acid, umbu-cajá pulp), unlike mangaba 5 , 60% (ferulic acid). The results obtained in this work demonstrate that the pulp consumption of these fruits, especially seriguela and umbu-cajá can contribute significantly to the ingestion of antioxidant compounds, since they have high concentration of bioaccessible phenolic compounds.